Genotypic and phenotypic spectrum of CCDC141 variants in a Chinese cohort with congenital hypogonadotropic hypogonadism. Issue 3 (September 2020) - Hou, Qiao; Wu, Jiayu; Zhao, Yaguang; Wang, Xinying; Jiang, Fang; Chen, Dan-Na; Zheng, Ruizhi; Men, Meichao; Li, Jia-Da
Abstract : Objective: : To identify CCDC141 variants in a large Chinese cohort with congenital hypogonadotropic hypogonadism (CHH) and to assess the contribution of CCDC141 to CHH. Design: : Detailed phenotyping was conducted in CHH patients with CCDC141 variants and co-segregation analysis was performed, when possible. Methods: : Whole-exome sequencing was performed in 177 CHH patients and 450 unrelated, ethnically matched controls from China. Results: : Seven novel CCDC141 rare sequencing variants (RSVs) were identified in 12 CHH pedigrees. Four of the variants were private mutations; however, p.Q409X, p.Q871X and p.G1488S were identified in more than one patient. Up to 75% (9/12) of patients had mutations in other CHH-associated genes, which is significantly higher than CHH patients without CCDC141 RSVs. The co-segregation analysis for eight CHH families showed that 75% (6/8) CCDC141 RSVs were inherited from their fertile parents. Over half (58.3%, 8/18) of the patients exhibited other clinical deformities in addition to hypogonadism. One patient harbouring a CCDC141 RSV showed a reversal of CHH after sex-steroid replacement. Conclusions: : Our results broaden the genotypic spectrum of CCDC141 in CHH, as CCDC141 RSVs alone do not appear sufficient to cause CHH. The phenotypic spectrum in patients with CCDC141 RSVs is much wider than originally believed.